Analisis Modal Sosial Dalam Pelaksanaan Kerja Bakti Perbaikan Jalan di Dusun kalisumber, Desa Ciberes Kecamatan Patokbeusi, Kabupaten Subang - Moh. Aris Munandar; Hafiz Rafi Uddin; Alfa Bagas Putra Trinida (PT FORMOSA CENDEKIA GLOBAL, 2022)
The participation of community groups in being involved in justifying damaged roads can be obtained through strengthening social capital. The purpose of this study is to determine whether in this activity there is a dimension of social capital. This study uses qualitative research, using the method of discussion used is descriptive analysis. The results of this study stated that based on the dimensions: trust, norm value, and network. Dimensions of Trust in this community service activity, a sense of trust grows from an attitude of tolerance. The dimensions of the existing social norms are the existence of mutual respect and humanization of each other. As well as the network dimension, there are specialist networks among community groups.